A new mechanism for LKB1 activation. (4th May 2018) - Lee, Szu-Wei; Lin, Hui-Kuan
ABSTRACT: Liver kinase B1 (LKB1, also known as serine/threonine kinase 11, STK11) has been thought to be a constitutively active tumor suppressor that is activated by forming an active complex. Very recently, a new post-translational modification on LKB1 was identified that can regulate LKB1 activation and LKB1-mediated cancer cell survival under energy stress.